Organocatalytic sequential alpha-amination/corey-chaykovsky reaction of aldehydes: a high yield synthesis of 4-hydroxypyrazolidine derivatives - Kumar, B. Senthil; Venkataramasubramanian, V.; Sudalai, Arumugam (Organic Letters, 2012)
A tandem reaction of in situ generated a-amino aldehydes with dimethyloxosulfonium methylide under Corey-Chaykovsky reaction conditions proceeds efficiently to give 4-hydroxypyrazolidine derivatives in high yields with excellent enantio- and diastereoselectivities. This organocatalytic sequential method provides for the efficient synthesis of anti-1,2-aminoalcohols, structural subunits present in several bioactive molecules as well.

One-pot synthesis of cyclic carbonates from aldehydes, sulfur ylide, and CO2 - Aher, Ravindra D.; Kumar, B. Senthil; Sudalai, Arumugam (Synlett, 2014)
Treatment of aldehydes with sulfur ylide (CH2=SOMe2 or CH2=SMe2), in the presence of CO2 (1 atm) bubbled sequentially under mild conditions, produces cyclic carbonates in preparative yields. Sodium iodide formed in situ promotes the reaction between epoxide as intermediate and CO2 at ambient conditions, thus constituting a powerful metal-free synthesis of organic cyclic carbonates directly from aldehydes.
Keywords: Carbon dioxide; cyclic carbonates; cyclization; epoxides; Insertion